1993
DOI: 10.1136/jcp.46.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Bile reflux and intestinal metaplasia in gastric mucosa.

Abstract: Aim: To determine associations between enterogastric bile reflux and gastric mucosal pathology. Method: A retrospective study using fasting gastric juice bile acid measurements and antral or prestomal biopsy specimens from 350 patients, 66 of whom had previously undergone surgery that either bypassed or disrupted the pyloric sphincter.Results: Bile reflux was positively associated with reactive gastritis and negatively with Helicobacter pylon density. After stratification for previous surgery, age, and H pylon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
131
0
7

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(141 citation statements)
references
References 13 publications
3
131
0
7
Order By: Relevance
“…Such areas may also become malignant after long-term influence of refluxed bile (6,13). Obtained results do not show such intensity of changes as suggested by a number of sources (14,15,16). It may be due to a relatively short observation time, which is a consequence of the short lifespan of examined animals.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Such areas may also become malignant after long-term influence of refluxed bile (6,13). Obtained results do not show such intensity of changes as suggested by a number of sources (14,15,16). It may be due to a relatively short observation time, which is a consequence of the short lifespan of examined animals.…”
Section: Discussionmentioning
confidence: 65%
“…In patients who did not undergo any procedures, "bile reflux" can be asymptomatic and is by some sources treated as a physiological phenomenon (8,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Increased bile concentrations in the stomach are positively associated with intestinal metaplasia and particularly so in those individuals infected with H. pylori. 5 The incidence of cancer in patients who have previously been operated on for duodenal ulcer is higher than the normal population, in spite of the fact that two-thirds of the stomach may have been removed at the original operation. This Ôsurgical experimentÕ is important because unoperated patients with duodenal ulcer are at lower risk of gastric cancer than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical application of Bilitec 2000 technology for the 24 h bile reflux monitoring revealed that bile reflux into the stomach or even the esophagus was a frequent phenomenon (1-3). Dixon et al believed that bile reflux might be related to the intestinal metaplasia of gastric antral mucosa (4)(5)(6). Recent studies have shown that bile reflux is not only related to reflux esophagitis but also is a significant cause of Barrett's esophagus (7)(8)(9)(10)(11) and esophageal adenocarcinoma (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%